The contribution of the gut-liver axis to the immune signaling pathway of NAFLD - Liu, Jiayi; Wu, Anding; Cai, Jingjing; She, Zhi-Gang; Li, Hongliang (Frontiers in Immunology, 2022)
Nonalcoholic fatty liver disease (NAFLD) is the liver manifestation of metabolic syndrome and is the most common chronic liver disease in the world. The pathogenesis of NAFLD has not been fully clarified; it involves metabolic disturbances, inflammation, oxidative stress, and various forms of cell death. The “intestinal-liver axis” theory, developed in recent years, holds that there is a certain relationship between liver disease and the intestinal tract, and changes in intestinal flora are closely involved in the development of NAFLD. Many studies have found that the intestinal flora regulates the pathogenesis of NAFLD by affecting energy metabolism, inducing endotoxemia, producing endogenous ethanol, and regulating bile acid and choline metabolism. In this review, we highlighted the updated discoveries in intestinal flora dysregulation and their link to the pathogenesis mechanism of NAFLD and summarized potential treatments of NAFLD related to the gut microbiome.